Touching matters: an ethnographic study of adult-child relationships and the use of touch in residential child care - Warwick, Lisa M. (2017)
This thesis explores adult-child relationships and the use of touch in residential child care. The discourses surrounding touch in residential child care are distinctly polarised: touch is identified as being both fundamental to child development and also feared as a result of increasing risk aversion resulting from the legacy of abuse scandals in the sector (Cooke, 2003; Steckley, 2012). There is currently a dearth of empirical research regarding how touch is used in residential child care, particularly with regards to observations of touch in practice. This research therefore contributes to filling this gap in research by utilising ethnographic methods of participant observation, semi-structured and ethnographic interviews to explore how staff members and children conceptualise, use and/or avoid physical touch in day-to-day practice. This research is examined through a lifespace framework and draws upon theories of intimacy in order to link the findings to wider sociological theories of relationships (Smith, 2005; Jamieson, 1998, 2011). By carrying out sustained observations of practice, this research examines how touch, as a facet of adult-child relationships in residential child care, is negotiated within the lifespace. It shows how intimacy is both cultivated and inhibited, thus contributing theoretically to wider sociological debates concerning adult-child relationships and touching practices, particularly in relation to professional relationships and intimacy (Morgan, 2009; Ferguson, 2011a). The fieldwork for this project took place over 6 months at Sunnydale House, a local authority children’s home in England. The findings suggest that touch is used much more regularly than has been previously suggested in literature (Ward, 1999; Cooke, 2003), that the majority of touch is instigated by children not workers and that recent organisational culture shifts have shaped the way that workers conceptualise touch. The findings also illustrate the complex range of factors which influence how touch is inhibited, including: risk aversion, emotional burn out, bureaucracy and the construction of children in care as ‘moral dirt’ (Ferguson, 2007). The thesis concludes by producing a typology of touching practices which synthesises the range of meanings behind the uses - and avoidance - of touch in residential child care practice. This typology is also used to re-conceptualise intimacy in professional relationships in a way that accounts for the messy ambiguity of adult-child relationships in the lifespace.